Acute Diarrhea Patients among Children Under Five Hospitalized in a Tertiary Hospital in East Java, Indonesia - Adiba, Asmahan Farah; Soedarmo, Subijanto Marto; Sulistiawati, Sulistiawati; Athiyyah, Alpha Fardah (Folia Medica Indonesiana, 2022)
Highlight: • The characteristics of acute diarrhea patients among chidren in Tertiary Hospital In East Java was evaluated. • The highest incidence of diarrhea was found in the 0-24 months age group, good nutritional status, male sex, and hospitalized in less than 5 days. • Mild-moderate dehydration, intravenous rehydration treated, anemia, hyponatremia, and metabolic acidosis were mostly founded. Abstract: Diarrhea is the second leading cause of morbidity and mortality in children under five years of age in Indonesia after pneumonia. In 2017, diarrhea became an outbreak in 12 provinces. Diarrhea in under-fives can cause several complications and can cause death if it is not treated properly. This study aimed to evaluate the characteristics of acute diarrhea patients in under-fives hospitalized in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia for six months. This study was a descriptive study with retrospective approach which evaluated all acute diarrhea patients hospitalized from July to December 2019. Patients' data were taken from medical records and presented descriptively. Of the total 125 patients, most acute diarrhea patients were male (60%) aged 0 to 24 months (83.2%), had good nutritional status (58.4%), and hospitalized for less than 5 days (60.8%). The most degree of dehydration was mild-moderate dehydration (83.2%), mostly treated with intravenous rehydration (96.8%), the most common comorbidity was anemia (13.4%), and the most electrolyte disorder was hyponatremia (41%), while acid-base disorder was mostly metabolic acidosis (75%).